Evaluation of supplementary carnosine accumulation and distribution: an initial analysis of participants in the Nucleophilic Defense Against PM Toxicity (NEAT) clinical trial - Shahid P. Baba; Alok R. Amraotkar; David Hoetker; Hong Gao; Daniel Gomes; Jingjing Zhao; Michael F. Wempe; Peter J. Rice; Andrew P. DeFilippis; Shesh N. Rai; C. Arden Pope; Aruni Bhatnagar; et al. (Amino Acids)
Abstract Carnosine is an endogenous dipeptide that buffers intracellular pH and quenches toxic products of lipid peroxidation. Used as a dietary supplement, it also supports exercise endurance. However, the accumulation and distribution of carnosine after supplementation has not been rigorously evaluated. To do this, we randomized a cohort to receive daily supplements of either placebo or carnosine (2 g/day). Blood and urine samples were collected twice over the subsequent 12 week supplementation period and we measured levels of red blood cell (RBC) carnosine, urinary carnosine, and urinary carnosine-propanol and carnosine-propanal conjugates by LC/MS–MS. We found that, when compared with placebo, supplementation with carnosine for 6 or 12 weeks led to an approximate twofold increase in RBC carnosine, while levels of urinary carnosine increased nearly sevenfold. Although there were no changes in the urinary levels of carnosine propanol, carnosine propanal increased nearly twofold. RBC carnosine levels were positively associated with urinary carnosine and carnosine propanal levels. No adverse reactions were reported by those in the carnosine or placebo arms, nor did carnosine supplementation have any effect on kidney, liver, and cardiac function or blood electrolytes. In conclusion, irrespective of age, sex, or BMI, oral carnosine supplementation in humans leads to its increase in RBC and urine, as well as an increase in urinary carnosine-propanal. RBC carnosine may be a readily accessible pool to estimate carnosine levels. Clinical trial registration: This study is registered with ClinicalTrials.gov (Nucleophilic Defense Against PM Toxicity (NEAT Trial)—Full Text View—ClinicalTrials.gov), under the registration: NCT03314987.